INFLUENCE OF ELECTRICITY CONSUMERS ON THE AUTONOMOUS POWER SUPPLY SYSTEMS VOLTAGE FORM - I. I. Zolotov; A. A. Shevcov (Известия высших учебных заведений: Проблемы энергетики)
Abstract: This article presents the results of a research concerning evaluation of the nature and influence degree of electricity consumers on the form of the autonomous power supply systems voltage, using the example of the BES-3000RM gasoline generator. Oscillograms of the work of a gasoline generator with active, inductive and parametric loads are presented, and for each of the experiments carried out, the main electrical parameters of the system inclusive gasoline generator and load were calculated and measured. The internal inductance and the active resistance of the BES-3000RM gasoline generator were calculated. The main negative influences for the sensitive load supplying process due presence of gasoline generator internal inductance and active resistance were indicated.